Το εκκλησιαστικό έγκλημα της εισαγωγής κτήνους σε ιερό ναό (2002)
The 88th Canon of  the Synod in Tullo (Trullo 88), punishing the crime of importing animal at church, remained for centuries at the backstage of canonical research, undermined, forgotten and misunderstood. This survey, brings the canon to the forefront, and spotlights its content as a most singnificant disclosure of the structure and theory of Church Criminal Law. The book is a manual of the General Part of Church Criminal Law: The action, the hypostasis of the crime, reasons of  lifting the unjust, external terms of criminality, criminal liabilty  are investigated in this "byzantine" canon. Last but not least:  a) we analyse how  the General Principle of  placing the Rights  Human Life and Health at the top of the Pyramid of Canonical Protection is provided by the Trullo 88 and is introduced to the whole Canon Law, b) we notice  the fact that the Canon introduces the Evangelic speech about the Sabbath into the field of Church Law, with serious consequences in the "philosophy" (=theology) of Orthodox Canon Law.